2005
DOI: 10.4049/jimmunol.175.6.3707
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement for CD28/CTLA-4-CD80/CD86 Interactions in Drug-Induced Type 1 and Type 2 Immune Responses to Trinitrophenyl-Ovalbumin

Abstract: The use of mAbs to abrogate costimulatory interactions has attracted much attention with regard to prevention and modulation of adverse (auto)immune-like reactions. However, the role of costimulatory molecules and possible therapeutic use of Ab-treatment in drug-induced immunostimulation is poorly elucidated. In the present studies, we show that CD28/CTLA-4-CD80/CD86 costimulatory interactions differently regulate drug-induced type 1 and type 2 responses to an identical bystander Ag, TNP-OVA, in BALB/c mice us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Moreover, monocytes of very-preterm neonates show a lack of response to IFN-␥ [11,38], which agrees with the fact that since it is usually synthesized by T h 1 lymphocytes, it generates a monocyte/macrophagelike costimulatory signal that induces or increases the expression of the B7-family receptors [39]. Besides T cell activation, the expression of B7 family molecules has an effect on cytokine production [40], and some authors have described a relationship between the expression of costimulatory molecules and the type of immune response developed [41]. The lack of expression of CD80 molecule, as well as IFN-␥ responses, observed in very-preterm neonates indicates that these infants could have an incomplete T h 1 response when confronted with the pathogen.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, monocytes of very-preterm neonates show a lack of response to IFN-␥ [11,38], which agrees with the fact that since it is usually synthesized by T h 1 lymphocytes, it generates a monocyte/macrophagelike costimulatory signal that induces or increases the expression of the B7-family receptors [39]. Besides T cell activation, the expression of B7 family molecules has an effect on cytokine production [40], and some authors have described a relationship between the expression of costimulatory molecules and the type of immune response developed [41]. The lack of expression of CD80 molecule, as well as IFN-␥ responses, observed in very-preterm neonates indicates that these infants could have an incomplete T h 1 response when confronted with the pathogen.…”
Section: Discussionsupporting
confidence: 68%
“…Popliteal lymph node assay (PLNA), a straightforward animal test, has been recognized as a simple tool that is a reliable, fast and reproducible method for IDHR assessment (Carey et al, 2006;Gehrs and Smialowicz, 1999;Gutting et al, 2002b;Kammuller et al, 1989;Lovik et al, 2007;Nierkens et al, 2005a). Since 1976, PLNA has been used to study graft vs host reactions, initially by Gleichmann and Gleichmann, and studies have demonstrated that numerous drugs and chemicals known to induce IDHR in humans, such as penicillin, diclofenac and cadmium, cause PLN reactions following injection into the footpad (Aida et al, 1998;Carey et al, 2006;Gleichmann and Gleichmann, 1976;Gutting et al, 2002b;Samuelsen et al, 2008); the results of these tests showed close correlations.…”
Section: Introductionmentioning
confidence: 99%